Allah Transenden yang Ditangguhkan: Kristus Pengharapan Eskatologis dalam Jürgen Moltmann dan Slavoj Žižek - Albungkari Albungkari (Faculty of Theology Duta Wacana Christian University, 2022)
Abstract This article aims to offer suspended transcendent God as an alternative for the thoughts of Jürgen Moltmann and Slavoj Žižek. Although they place Christ as the basis of eschatological hope, they have different opinions regarding the involvement of a transcendental entity (God). If Moltmann emphasizes on God’s intervention in the fulfillment of eschatological expectations Žižek rejects the involvement of transcendental entities by assuming that the divine has died so that the responsibility is transferred to humans. Departing from the lens of Ernst Bloch’s speculative materialism, this article concludes with a construction of a suspended transcendent God. This concept neither accepts nor rejects God’sintervention, but sees it as a speculative possibility. Abstrak Artikel ini bertujuan menawarkan Allah transenden yang ditangguhkan (suspended transcendent God) sebagai alternatif pemikiran Jürgen Moltmann dan Slavoj Žižek. Meskipun sama-sama menempatkanKristus sebagai dasar pengharapan eskatologis, akan tetapi keduanya berbeda pendapat perihal keterlibatan entitas transendental (Allah). Jika Moltmann sangat menekankan intervensi Allah dalam pemenuhan pengharapan eskatologis, maka Žižek menolak keterlibatan entitas transendental dengan menganggap yang Ilahi telah mati sehingga tanggung jawab tersebut dialihkan pada manusia. Berangkat dari lensa materialisme spekulatif Ernst Bloch, artikel ini ditutup dengan konstruksi mengenai Allahtransenden yang ditangguhkan. Konsep ini tidak menerima maupun menolak intervensi Allah, melainkan melihatnya sebagai kemungkinan spekulatif.